Hydraulic shotcrete containing anionic modified polymer and construction process

By using the use of yin -lying -type modified polymer exterior agents in water -spray concrete, the problem of poor transport stability and insufficient efficacy of the speed condensation are solved, and the effect of improving construction efficiency and support quality is achieved.

CN119349946APending Publication Date: 2025-01-24四川华能泸定水电有限公司 +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411099739.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-12
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

Hydraulic sprayed concrete has poor stability during transportation and insufficient effect of the fast condenser, resulting in insufficient strength and compactness during construction, a decrease in slump, affecting construction performance, and high construction costs and serious waste.

Method used

Adopt a combination of yin -ionized modified polymer as an outer agent, a combination of components such as embedded segments and nanocellulose, nano -silicon calcium oxides, etc., to form a stable water -based jet concrete outer agent material, improve Construction efficiency and support quality.

Benefits of technology

It improves the solid content and early strength of hydraulic sprayed concrete, enhances corrosion resistance and adhesion, adapts to complex and changeable hydraulic environments, and reduces construction and maintenance costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119349946A_ABST
    Figure CN119349946A_ABST
Patent Text Reader

Abstract

The invention discloses hydraulic shotcrete containing an anionic modified polymer and a construction process, which can effectively solve the problems of complex mixing operation and serious material cost waste in the construction process of the hydraulic shotcrete, and improve the construction efficiency and the supporting safety quality while being economical, friendly and environment-friendly. According to the preparation method, epoxypropyl methacrylate is homopolymerized through free radical polymerization, epoxy group ring opening is realized by using an ammonia water environment, and a copolymer is obtained through a double bond reaction of a formed amino intermediate and methacrylic acid, so that the adhesive force and weather resistance of the hydraulic shotcrete are enhanced, the ionic strength of the material is enhanced, and the service life of the hydraulic shotcrete is prolonged. The slump-retaining agent has better water dispersibility, so that the slump retention is facilitated; then, a three-dimensional skeleton structure is built with nano cellulose by taking nano silicon-calcium oxide particles as nodes, and a steric hindrance effect is generated, so that the stability of the system is improved, and the anti-cracking and anti-abrasion strength and the corrosion resistance coefficient of the hydraulic concrete are ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention provides hydraulic sprayed concrete containing anionic modified polymer and a construction process, belonging to the technical field of hydraulic sprayed concrete support. Background Art

[0002] During the excavation and construction of hydraulic tunnels, shotcrete is used as a temporary support technology. It uses compressed air to spray a mixture of cement, aggregate, water and admixtures onto the designed surface to make it gel into a concrete support measure. The supporting function of shotcrete is to reinforce the rock layer in time, prevent the loosening, peeling and falling of rock blocks, and enhance the stability of the rock mass. Since shotcrete is tightly bonded to the rock layer, it can evenly distribute the load transmitted by the surrounding rock, so as to make full use of the resistance of the rock layer. The rock interface of hydraulic tunnels is often in a humid state, and is greatly affected by complex environmental factors such as dry-wet cycles, water erosion, and ion erosion. It is prone to bubbling, peeling and shedding, resulting in poor durability of concrete, which is difficult to meet the construction needs of hydraulic structures.

[0003] At present, during the construction of hydraulic shotcrete tunnels, it is necessary to pre-mix the shotcrete mortar outside the tunnel, transport it to the tunnel construction area, and then add an accelerator before the shotcrete operation. If the mixing time is too short, the strength and density of the concrete will be insufficient. If the mixing time is too long, the slump of the concrete will decrease, affecting the construction performance of the concrete. The water diversion tunnel usually has complex geological conditions and a long construction mileage, which places high requirements on the construction management and equipment conditions of the shotcrete operation, resulting in high construction costs and serious waste. Summary of the invention

[0004] The invention provides a construction process for hydraulic sprayed concrete containing anionic modified polymers, and aims to solve the technical problems of poor transportation stability and insufficient effectiveness of accelerators of existing hydraulic sprayed concrete. Molecular design is performed on early strength agents, polyether polyamines are used to form active amine groups, which react with double bonds in acrylic monomers to obtain block copolymers, thereby obtaining a hydraulic sprayed concrete admixture material with good stability, high solid content, safety, environmental protection and easy operation, thereby improving construction efficiency and support quality.

[0005] The technical solution of the present invention: A hydraulic sprayed concrete containing anionic modified polymer has a strength grade of C25. The raw material components mainly include cementitious materials, aggregates, water and anionic modified polymer admixtures. The mix ratio of the hydraulic sprayed concrete is as follows: the amount of cementitious materials is 420-440 kg / m³, the water-binder ratio is 0.44-0.45, the sand ratio is 58%, and the amount of the anionic modified polymer admixture is 5% of the total amount of the cementitious materials.

[0006] Furthermore, the cementitious material is silicate cement with a strength grade of 42.5R or above.

[0007] Furthermore, the aggregate can be coarse aggregate and fine aggregate, and the weight ratio of coarse aggregate to fine aggregate is 1.38:1; the coarse aggregate is 5-15 mm pebbles, with a crushing index of ≤8%, a total content of needle- and flake-like particles ≤4%, a mud content ≤0.5%, and a tight void ratio ≤40%; the fine aggregate is medium-coarse river sand with a fineness modulus of 2.7-3.2, a mud content ≤2.0%, and a mud block content ≤0.5%.

[0008] Furthermore, the anionic modified polymer admixture comprises the following components in parts by mass: Block copolymer dispersant: 5-20 parts; Nanocellulose: 0.5-5 parts; Nano-silicon calcium oxide: 2-10 parts; Accessories: 2-10 parts; Solvent water: 60-85 parts.

[0009] Furthermore, the nanocellulose is one or more of cellulose nanofibers, cellulose nanocrystals, sulfonated cellulose nanocrystals, carboxylated nanocellulose hydrogels, phosphorylated cellulose nanofibers, amphiphilic cellulose nanofibers, and amphiphilic cellulose nanocrystals.

[0010] Further, the nano-silicon calcium oxide is an oxide particle with a particle size of less than 250 nm, preferably an oxide particle with a particle size of less than 200 nm, and more preferably an oxide particle with a particle size of less than 100 nm. The chemical formula of the nano-silicon calcium oxide can be expressed as xCaO·SiO2·yH2O+zCa(OH)2 or xCaO·SiO2·yH2O+zSi(OH)4, wherein x=0.8~2.0, y=4~12, and z=0~2.2, and the value depends on the total ratio of calcium element to silicon element.

[0011] Furthermore, the auxiliary material is one or more of sodium chloride, sodium nitrate, sodium nitrite, sodium sulfate, sodium gluconate, potassium chloride, potassium nitrate, potassium nitrite, and potassium sulfate.

[0012] A construction process for hydraulic sprayed concrete containing anionic modified polymers, characterized by comprising the following steps: 1) Construction preparation: Check the size of the excavation section, pry off the loose soil and under-excavated parts on the surface, remove the scum and the sprayed surface, drive short steel bars into the rock surface, and mark the scale; if there is a large amount of water on the excavation surface, drain the water in a centralized manner; 2) Preparation of anionic modified polymer admixtures; 3) Shotcrete mixing: According to the mix ratio requirements, it is mixed centrally at the mixing station outside the tunnel, the slump is controlled at 100~120mm, and it is transported to the tunnel by concrete tank trucks; 4) Spraying operation: Use wet spraying technology to first spray 3cm thick concrete to seal the soil surface, set up steel frames, hang steel mesh, install locking anchor rods, clean the initial sprayed soil surface and then spray again to the designed thickness; 5) Concrete curing: Use a sprayer to cure for more than 7 days 24 hours after final setting.

[0013] As a preferred solution, the spraying operation in step 4) is carried out in layers, sections and slices in a continuous order from bottom to top; firstly, the low-lying areas are roughly sprayed flat, and then the layers are sprayed back and forth in sequence; As a preferred solution, during the layered spraying, the thickness of each layer of the top arch is about 5 to 8 cm, and the thickness of each layer of the side wall is 8 to 15 cm, and the thickness of the sprayed layer is kept uniform; the segment length is less than 6 m; the piecewise spraying is carried out from bottom to top, first spraying the concrete between the steel frame and the soil surface, and then spraying the concrete between the two steel frames.

[0014] As a preferred solution, during spraying, the nozzle is kept at a distance of 0.8 to 1.2 m from the sprayed surface, and the spraying angle is as close to 90° as possible; the working wind pressure of the spraying equipment is 0.6 MPa.

[0015] Beneficial effects of the present invention: 1) The addition of methacrylic acid-glycidyl methacrylate block copolymer enhances the ionic strength of the admixture, provides better water dispersibility, and is beneficial to increasing the solid content. In concrete applications, it can accelerate the setting time and improve the early strength; 2) Nanocellulose and dispersant jointly construct a three-dimensional skeleton, and the pore points are modified with nano-silicon calcium oxide particles to produce a steric hindrance effect, thereby improving the corrosion resistance coefficient of hydraulic concrete and reducing the shrinkage caused by the carbonization process; 3) The copolymer has strong designability and small particle size, which can enhance the adhesion and weather resistance of concrete to adapt to the complex and changeable hydraulic environment. It is economical, friendly, green and environmentally friendly, while improving construction efficiency and greatly reducing construction and maintenance costs. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work. Among them: Figure 1 The present invention is a construction process flow chart of hydraulic sprayed concrete containing anionic modified polymer. DETAILED DESCRIPTION

[0017] The preparation method of anionic modified polymer admixture comprises the following steps: S1: Preparation of block copolymer dispersant: S11: Preparation of poly(glycidyl methacrylate) by homopolymerization: adding an initiator to a solution of glycidyl methacrylate monomer and mixing uniformly to obtain a mixed solution A; adding a dispersant to a mixed solution of ethanol and water and mixing uniformly to obtain a mixed solution B; heating the mixed solution B to 70° C. under the protection of an inert gas, then adding the mixed solution A, and keeping the mixture warm for a full reaction of 10 hours; the product is centrifuged several times, washed with alcohol, and then dried to obtain poly(glycidyl methacrylate); The initiator is one or more of polyethylene glycol, 2-acrylamide-2-methylpropane sulfonic acid, sodium methyl allyl sulfonate, β-mercaptopropionic acid, thioglycolic acid, persulfate, azobisisobutyronitrile, diacyl peroxide, and sodium gluconate; the dispersant is polyvinyl pyrrolidone; S12: Epoxy ring opening to form active amine group: At room temperature, the poly(glycidyl methacrylate) of S11 was soaked in ammonia water for 24 hours, then washed with deionized water to remove excess ammonia water, and dried at low temperature to obtain an amine intermediate; S13: Initiation of double bond reaction: Under the protection of inert gas, the re-prepared mixed solution B is heated to 60°C, and then a mixed solution of the amino intermediate and the initiator is added, and after stirring evenly, methacrylic acid monomer is added dropwise, and the reaction is carried out for 3 hours; the product is centrifuged several times, washed with alcohol, and then dried to obtain a methacrylic acid-methacrylic acid epoxypropyl block copolymer dispersant.

[0018] S2: fully mixing the block copolymer dispersant and nanocellulose to obtain a dispersion; S3: Add calcium nitrate solution and sodium silicate solution to the dispersion in S2 at the same time, and stir continuously to generate nano-silicon calcium oxide, add auxiliary materials, stir continuously for 24 hours and age, and obtain an anionic modified polymer admixture.

[0019] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the present invention is described in detail below in conjunction with the embodiments of the specification.

[0020] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0021] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments. Example

[0022] Preparation of anionic modified polymer admixtures: 1) Add 0.05 parts of dispersant polyvinyl pyrrolidone (PVP) dissolved in 150 ml of ethanol and water and heat to 70°C, then add 40 parts of monomer GMA dissolved in initiator AIBN, and react for 10 hours under nitrogen protection. Then, centrifuge and wash the polymer dispersion with alcohol several times, and dry it to obtain PGMA.

[0023] 2) Soak in 0.3 mol ammonia water at room temperature for 24 hours. After the reaction, wash the particles with water several times to remove excess ammonia water, and store the amino intermediates after low-temperature drying.

[0024] 3) Heat a mixture of 150 ml of ethanol and water containing 0.05 parts of PVP to 60°C in a water bath, then add an amino intermediate containing 0.9 parts of ammonium persulfate, and under the protection of nitrogen, add a reaction monomer methacrylic acid aqueous solution (0.48 g / ml, 50 ml) dropwise at a constant rate. After reacting for 3 hours, the polymer dispersion is centrifuged and washed with water several times, and then dried to obtain a methacrylic acid-methacrylic acid glycidyl ester block copolymer dispersant.

[0025] 4) fully mixing the block copolymer dispersant with 0.5 parts of nanocellulose to obtain a dispersion; 5) 10 parts of calcium nitrate solution and 10 parts of sodium silicate solution are simultaneously dripped into the dispersion in step 4) and stirred continuously to generate nano-silicon calcium oxide, and 10 parts of auxiliary materials are added and stirred continuously for 24 hours for aging to obtain anionic crystal gel modified polymer. The auxiliary materials are sodium nitrate, sodium gluconate, sodium sulfate, and potassium chloride in a ratio of 5:3:2:1.

[0026] The properties of the anionic modified polymer admixture prepared in this embodiment are as follows: (1) Solid content: 58%; (2) Viscosity: 74 mPa·S; (3) Average particle size: 226 nm; (4) Centrifugal stability: 4000r / min, no stratification and no demulsification for 30min; (5) Dilution stability: dilute with water to 1~3% and leave for 48 hours, the emulsion will not separate or break; (6) Acid and alkali stability: Acid and alkali are added to the emulsion, and the stable pH range is 6-8; (7) High temperature stability: Heating at 100°C for 1 hour, leaving at room temperature for 5 hours, and repeating this process 6 times, the emulsion is stable without stratification or demulsification; (8) Freeze-thaw stability: Freeze at -30°C for 6 hours, place at room temperature for 8 hours, and repeat this process 7 times. The emulsion is stable without stratification or demulsification.

[0027] The process test was carried out, and the materials used were as follows: ① the cement used was P·O 42.5R produced by Sichuan Erlangshan Labahe Cement Co., Ltd.; ② the fine and coarse aggregates used were produced by China Water Resources and Hydropower No. 10 Engineering Bureau Co., Ltd.; ③ the water used was Mozigou surface drinking water; and ④ the admixture was the anionic modified polymer admixture prepared by this method.

[0028] The test hydraulic sprayed concrete mix ratio is as follows:

[0029] Take the 100×100×100mm specimens cut from the large plate on the test site for compression test. The 8h, 16h, 24h, 3d, and 28d strength comparison of the large plate cut specimens is used to evaluate the concrete strength. The average rebound value of the on-site test spraying is taken to evaluate the rebound rate of the sprayed concrete. The comparison data are as follows:

[0030] In the on-site spraying test, the test site was selected in a place with water seepage, and the concrete mixing was completed outside the test tunnel. The test spraying was carried out after transportation and commissioning. The whole spraying process on site was smooth and the appearance was round.

[0031] The above is only a preferred specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A hydraulic sprayed concrete containing anionic modified polymer, with a strength grade of C25, characterized in that The raw material components mainly include cementitious materials, aggregates, water and anionic modified polymer admixtures; The amount of the cementitious material is 420-440 kg / m³, the water-cement ratio is 0.44-0.45, the sand ratio is 58%, and the amount of the anionic modified polymer admixture is 5% of the total amount of the cementitious material.

2. The hydraulic sprayed concrete containing anionic modified polymer according to claim 1, characterized in that The cementitious material is silicate cement with a strength grade of 42.5R or above; the aggregate may be coarse aggregate and fine aggregate, and the weight ratio of the coarse aggregate to the fine aggregate is 1.38:1; The coarse aggregate is 5-15 mm pebbles, with a crushing index of ≤8%, a total content of needle-shaped and flake-shaped particles of ≤4%, a mud content of ≤0.5%, and a tight void ratio of ≤40%; the fine aggregate is medium-coarse river sand with a fineness modulus of 2.7-3.2, a mud content of ≤2.0%, and a mud block content of ≤0.5%.

3. The hydraulic sprayed concrete containing anionic modified polymer according to claim 1, characterized in that The anionic modified polymer admixture comprises the following components in parts by mass: Block copolymer dispersant: 5-20 parts; Nanocellulose: 0.5-5 parts; Nano-silicon calcium oxide: 2-10 parts; Accessories: 2-10 parts; Solvent water: 60-85 parts.

4. The hydraulic sprayed concrete containing anionic modified polymer according to claim 3, characterized in that The nanocellulose is one or more of cellulose nanofibers, cellulose nanocrystals, sulfonated cellulose nanocrystals, carboxylated nanocellulose hydrogels, phosphorylated cellulose nanofibers, amphiphilic cellulose nanofibers, and amphiphilic cellulose nanocrystals; the nano-silicon calcium oxide is oxide particles with a particle size of less than 250 nm; and the auxiliary material is one or more of sodium chloride, sodium nitrate, sodium nitrite, sodium sulfate, sodium gluconate, potassium chloride, potassium nitrate, potassium nitrite, and potassium sulfate.

5. A construction process for hydraulic sprayed concrete containing anionic modified polymers, characterized in that The following steps are involved: 1) Construction preparation: Check the size of the excavation section, pry off the loose soil and under-excavated parts on the surface, remove the scum and the sprayed surface, drive short steel bars into the rock surface, and mark the scale; if there is a large amount of water on the excavation surface, drain the water in a centralized manner; 2) Preparation of anionic modified polymer admixtures; 3) Shotcrete mixing: According to the mix ratio requirements provided in claims 1 and 2, it is mixed centrally at a mixing station outside the tunnel, the slump is controlled at 100-120mm, and it is transported to the tunnel by concrete tank trucks; 4) Spraying operation: Use wet spraying technology to first spray 3cm thick concrete to seal the soil surface, set up steel frames, hang steel mesh, install locking anchor rods, clean the initial sprayed soil surface and then spray again to the designed thickness; 5) Concrete curing: Use a sprayer to cure for more than 7 days 24 hours after final setting.

6. The construction process of hydraulic sprayed concrete containing anionic modified polymer according to claim 5, characterized in that Step 2) The preparation of the anionic modified polymer admixture comprises the following steps: S1: preparing the block copolymer dispersant of claim 3: preparing poly(glycidyl methacrylate) by homopolymerization of glycidyl methacrylate; adding ammonia water to open the epoxy group to form an active amine group; initiating the reaction of the active amine group with the double bond in methacrylic acid by an initiator, and finally obtaining a block copolymer of methacrylic acid and glycidyl methacrylate, which is the block copolymer dispersant; S2: fully mixing the block copolymer dispersant with the nanocellulose according to claim 4 to obtain a dispersion; S3: Add calcium nitrate solution and sodium silicate solution to the dispersion liquid described in S2 at the same time, and stir continuously to generate the nano-silicon calcium oxide described in claim 3, add the auxiliary material described in claim 4, stir continuously for 24 hours and age, and obtain an anionic modified polymer admixture.

7. The construction process of hydraulic sprayed concrete containing anionic modified polymer according to claim 6, characterized in that The preparation of the block copolymer dispersant described in S1 specifically comprises the following steps: S11: Preparation of poly(glycidyl methacrylate): adding an initiator to a monomer solution of glycidyl methacrylate and mixing them uniformly to obtain a mixed solution A; adding a dispersant to a mixed solution of ethanol and water and mixing them uniformly to obtain a mixed solution B; under the protection of an inert gas, heating the mixed solution B to 70° C., then adding the mixed solution A, and keeping the temperature to fully react for 10 hours; the product is centrifuged several times, washed with alcohol, and then dried to obtain poly(glycidyl methacrylate); S12: At room temperature, the poly(glycidyl methacrylate) obtained in S11 is soaked in ammonia water for 24 hours, then washed with deionized water to remove excess ammonia water, and dried at low temperature to obtain an amino intermediate; S13: Under the protection of inert gas, the re-prepared mixed solution B is heated to 60°C, and then a mixed solution of the amino intermediate and the initiator is added, and after stirring evenly, methacrylic acid monomer is added dropwise, and the reaction is carried out for 3 hours; the product is centrifuged several times, washed with alcohol, and then dried to obtain a methacrylic acid-methacrylic acid epoxypropyl block copolymer dispersant.

8. The construction process of hydraulic sprayed concrete containing anionic modified polymer according to claim 7, characterized in that The initiator is one or more of polyethylene glycol, 2-acrylamide-2-methylpropane sulfonic acid, sodium methyl allyl sulfonate, β-mercaptopropionic acid, thioglycolic acid, persulfate, azobisisobutyronitrile, diacyl peroxide, and sodium gluconate; the dispersant described in step S11 is polyvinyl pyrrolidone.

9. The construction process of hydraulic sprayed concrete containing anionic modified polymer according to claim 5, characterized in that Step 4) The spraying operation is carried out in layers, sections and slices in a continuous order from bottom to top; first, the low-lying areas are roughly sprayed flat, and then the layers are sprayed back and forth in sequence; During the layered spraying, the thickness of each layer of the top arch is about 5 to 8 cm, and the thickness of each layer of the side wall is 8 to 15 cm, and the thickness of the sprayed layer is kept uniform; the length of the segment is less than 6 m; The piecewise spraying is carried out from bottom to top, first spraying the concrete between the steel frame and the soil surface, and then spraying the concrete between the two steel frames.

10. The construction process of hydraulic sprayed concrete containing anionic modified polymer according to claim 9, characterized in that During spraying, the nozzle should be kept at a distance of 0.8 to 1.2 m from the sprayed surface, and the spraying angle should be as close to 90° as possible; the working air pressure of the spraying equipment is 0.6 MPa.